PERBEDAAN HASIL BELAJAR DAN KEMAMPUAN BERPIKIR KRITIS SISWA YANG DIAJAR DENGAN MENGGUNAKAN MEDIA HANDOUT DAN POWER POINT PADA MATERI LARUTAN PENYANGGA - Dewi Syafriani; Sisca Jenifer (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2019)
This study aims to determine the differences in learning outcomes and critical thinking ability of students who are taught by the model of Problem Based Learning using the media handout and power point. The population in this study were all students of class XI SMA Negeri 1 Berastagi. Sampling was done by random sampling. Then hypothesis testing is conducted using a two-party test of Independent Sample T-Test. To test the hypothesis I obtained results sig. 0,018 (sig. < 0,5) which means there is a significant difference in students' learning outcomes who are taught by the model of Problem Based Learning using the media handout compared learning outcomes of students who are taught by the model of Problem Based Learning using media power point on the material buffer solution. To test the hypothesis II result sig. 0,001 (sig. <0,5) which means there is a significant difference in students' critical thinking ability who are taught by the model of Problem Based Learning using the media handout than students' critical thinking ability who are taught by the model of Problem Based Learning using media power point on the material buffer solution.Keywords: Problem Based Learning, Handouts, Buffer Solution.